Effects of hepatitis B vaccine boosters on anti-HBs-negative children after primary immunization. Issue 4 (3rd April 2017) - Lu, Shunshun; Ren, Jingjing; Li, Qian; Jiang, Zhenggang; Chen, Yongdi; Xu, Kaijin; Ruan, Bing; Yang, Shigui; Xie, Tiansheng; Yang, Linna; Li, Jing; Yao, Jun
ABSTRACT: This study was aimed at evaluating the changes of hepatitis B surface antibody (anti-HBs) titer after booster vaccinations in 5–15-year-old children with negative antibodies (<10 mIU/mL). 225 subjects (mean age, 9.28 ± 2.95 years) included in the study consisted of 123 males and 102 females, with a complete hepatitis B vaccination during infancy. The participants were divided into 3 groups according to their pre-booster anti-HBs level: Group I, <0.1 mIU/mL; Group II, 0.1 to <1.0 mIU/mL; Group III, 1.0 to <10.0 mIU/mL. All the participants were administered 3 doses of booster hepatitis B vaccination (0-1-6 month, 20 µg), and changes in the levels of antibodies were examined at 4 time-points (one month after the first and the third dose, one year and 5 years after the third dose). The seroprotective rate (defined as anti-HBs ≥10.0 mIU/mL) among 225 subjects at the 4 time-points were 93.8%, 100%, 83.6% and 73.4%, respectively ( χ 2 = 90.29, p < 0.05). The seroprotective rate (≥10 mIU/mL) and anti-HBs geometric mean titer (GMT) in Group III were always higher than those in the other 2 groups (all p < 0.05). The immune effect of a 3 -dose booster revaccination is good, and the booster-induced immune response was correlated with the pre-booster titer level, and ≥1.0 mIU/mL ensuring a robust positive response, whereas titers below this value may indicate the need for a course of booster vaccination.